Communicative Language Teaching in Indonesia: Issues of Theoretical Assumptions and Challenges in the Classroom Practice - Musthafa, Bachrudin (TEFLIN Journal, 2015)
Trying to keep abreast to recent development in ESL pedagogy, Indonesian Government in this case Ministry of National Education has for the past two decades been trying to reform English instruction at the junior and senior high schools across the country. This article describes the issues surrounding the reform initiative and the response the system has made to address the issues. The existing, problematic conditions are delineated and possible ways for improvement are then put forth.